Energy Development and Climate Change Concerns: Legal and Policy Appraisal from Cameroon (African Journal of Law and Politics, 2025)
This article sets out to ascertain the level of attention that climate change receives under theCameroonian energy legal and policy framework, more particularly how it supports the developmentof low-greenhouse gas (GHG) energy or a climate-friendly energy system in Cameroon. The articleshowcases the climate change implications of energy development in Cameroon and maps the policyguidelines for the development of a low-GHG energy system under the Cameroonian climate changeand energy legal and policy instruments. Building on both primary and secondary data and employingthe doctrinal research method and the content analysis approach, this article argues that theCameroonian energy legal and policy framework does not adequately address climate change concerns.The findings reveal that the Cameroonian energy legal and policy frameworks do not adequately supportthe development of a climate-friendly energy system. Consequently, the potential of the energy sectorin contributing to the fight against climate change in terms of mitigation may not be fully tapped. Basedon the findings, what is proffered as an important recommendation is the strong need for Cameroon toelaborate and implement holistic energy legal and policy frameworks that comprehensively take onboard climate change concerns. Such holistic energy legal and policy frameworks should set targets andtimelines for gradual transition from the development of high GHG emissions sources of energy to thedevelopment of low or zero GHG emissions sources of energy.